Evaluation of resection of the gastroesophageal junction and jejunal interposition (Merendino procedure) as a rescue procedure in patients with a failed redo antireflux procedure. A single-center experience - Apostolos Analatos; Mats Lindblad; Ioannis Rouvelas; Peter Elbe; Lars Lundell; Magnus Nilsson; Andrianos Tsekrekos; Jon A. Tsai (BMC Surgery, 2018)
Abstract Background Primary antireflux surgery has high success rates but 5 to 20% of patients undergoing antireflux operations can experience recurrent reflux and dysphagia, requiring reoperation. Different surgical approaches after failed fundoplication have been described in the literature. The aim of this study was to evaluate resection of the gastroesophageal junction with jejunal interposition (Merendino procedure) as a rescue procedure after failed fundoplication. Methods All patients who underwent a Merendino procedure at the Karolinska University Hospital between 2004 and 2012 after a failed antireflux fundoplication were identified. Data regarding previous surgical history, preoperative workup, postoperative complications, subsequent investigations and re-interventions were collected retrospectively. The follow-up also included questionnaires regarding quality of life, gastrointestinal function and the dumping syndrome. Results Twelve patients had a Merendino reconstruction. Ten patients had undergone at least two previous fundoplications, of which one patient had four such procedures. The main indication for surgery was epigastric and radiating back pain, with or without dysphagia. Postoperative complications occurred in 8/12 patients (67%). During a median follow-up of 35 months (range 20–61), four (25%) patients had an additional redo procedure with conversion to a Roux-en-Y esophagojejunostomy within 12 months, mainly due to obstructive symptoms that could not be managed conservatively or with endoscopic techniques. Questionnaires scores were generally poor in all dimensions. Conclusions In our experience, the Merendino procedure seems to be an unsuitable surgical option for patients who require an alternative surgical reconstruction due to a failed fundoplication. However, the small number of patients included in this study as well as the small number of participants who completed the postoperative workout limits this study.